Relationship between mother's oral health literacy level with oral hygiene behavior and self-reported oral health status in sociodemographic scope - Maudi, Tiarani; Suryanti, Netty; Setiawan, Asty Samiaty (Universitas Padjadjaran, 2023)
ABSTRACTIntroduction: Oral Health Literacy (OHL) plays an important role in reducing the gap in promoting oral health. Oral health literacy of mothers is important due to maternal OHL can affect the family's oral health, especially in children. Sufficient OHL of mothers also help strengthen their capacities to improve their own and their children's oral health. The purpose of this study was to analyze the oral health literacy level of mothers and its relationship to the oral hygiene behavior and self-reported oral health status in the sociodemographic scope. Methods: The type of research was correlational analytics with cross-sectional techniques. The samples were 158 mothers, collected using purposive sampling in Parigi District, Pangandaran Regency. Data were collected using the Health Literacy in Dentistry (HeLD-14) questionnaires which had been cross-adapted and included questions to assess oral hygiene behaviors with the Indonesian version of the oral hygiene behavior index. Data were analyzed using the Pearson correlation test and independent sample t-test. Results: The majority of mothers had a good educational level and did not get employment, and had a good level of oral health literacy, with an average score of 49.63±7.16. Dental hygiene behaviors were in the good category with a mean score of 3.13±0.82 and the results of self-assessment mostly stated that the oral and dental conditions were in a proper state. The results of the OHL correlation tests with oral hygiene behaviors and self-reported oral health status showed significant relations with low correlations (p=0.04; r=0.16) and (p=0.01; r=0.21). Conclusion: Mothers’ oral health literacy level is in good category and there are relations between oral dental health literacy with oral hygiene behaviors and self-reported oral health status.Keywords: oral health literacy, HeLD-14, oral hygiene behavior, sociodemographic, mother, oral health status